2010
DOI: 10.4236/jmmce.2010.912078
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Structural Characterization of Gadolinium Neodymium Oxalate Crystals Grown in Hydro-Silica Gel

Abstract: Gadolinium Neodymium Oxalate (GNO) single crystals were grown in hydrosilica gel by the diffusion of a mixture of aqueous solutions of the respective rare earth nitrates into a gel, impregnated with oxalic acid, in a test tube. Pink, transparent, hexagonal GNO crystals were obtained on optimization of growth parameters. The crystals are found to be monoclinic by the XRD analysis. The presence of water of hydration and carboxylic group in the grown crystals was confirmed by IR analysis. EDAX analysis confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Optical studies using UV‐vis spectroscopy showed extent of transparency of the crystals to the UV‐vis light, which helps in finding the energy gap of the sample …”
Section: Resultsmentioning
confidence: 99%
“…Optical studies using UV‐vis spectroscopy showed extent of transparency of the crystals to the UV‐vis light, which helps in finding the energy gap of the sample …”
Section: Resultsmentioning
confidence: 99%
“…The TGA curve has the usual shape already reported for lanthanide oxalates. 22,26 The total weight loss of 44.5 wt.% is significantly lower than the value of ∼53% observed in similar compound. 22,23 This indicates a low interstitial or "zeolitic" water content phase.…”
mentioning
confidence: 79%
“…Lanthanide oxalates were studied for a long time for their optical properties and are generally prepared in the form of single crystals. [20][21][22][23][24][25] They are also used as precursors for the synthesis of ceramics. 26,27 The phases usually described have the composition Ln 2 (C 2 O 4 ) 3 ·nH 2 O, a rich water phase presenting a weight loss of about 53% between 25 and 650…”
mentioning
confidence: 99%
“…Keskar et al [24] have carried out detailed study on thermal expansion of some other molybdates and tungstates such as Gd 2 Mo 3 O 12 and Gd 2 W 3 O 12 . Korah et al [25] reported the growth and structural characteristics of gadolinium neodymium oxalate crystals.…”
Section: Introductionmentioning
confidence: 99%